Keefektifan Penggunaan Model Pembelajaran VAK Dengan Memanfaatkan Media Dakota: Keefektifan Penggunaan Model Pembelajaran VAK Dengan Memanfaatkan Media Dakota - Anwar, Zakiyah; Budiarti, Marlinda Indah Eka; Maryam, Andi; Ahmad, Rizky Ekawati; Sarira, Regina Amelia (KAMBIK: Journal of Mathematics Education, 2023)
This research is an experimental research that aims to determine the effectiveness of using the Visualization, Auditory, Kinesthetic (VAK) learning model by utilizing Dakota media in class IV SD Muhammadiyah 2 Sorong City. This study used two control classes, namely the experimental class and the class. In the experimental class the visualization, auditory, kinesthetic (VAK) learning model was used combined with the use of dakota media, while in the control class the usual/conventional learning model was used. The research design used was The Non-Equivalent Pretest-posttest Control Group Design. The results showed that the application of the VAK learning model by utilizing dakota media effectively increased student learning outcomes in class IVB SD Muhammadiyah 2 Sorong City based on hypothesis testing where the result was a grade The 2-tailed sig t test (P-value) is 0.000 > 0.05 which means Ho is rejected. Based on the results of the screening analysis of learning effectiveness, it shows that teacher activity is in the very good category, student activity and responses are in the good category, and student learning outcomes are in the medium category with an average score obtained after treatment is 70 with an average N- obtained 0.57.